2004
DOI: 10.1021/la0485069
|View full text |Cite
|
Sign up to set email alerts
|

Novel Solid-State Polymer Electrolyte Consisting of a Porous Layer-by-Layer Polyelectrolyte Thin Film and Oligoethylene Glycol

Abstract: A novel solid-state polymer electrolyte was constructed using layer-by-layer (LbL) polyelectrolyte assembly of linear poly(ethylenimine) (LPEI) and poly(acrylic acid) (PAA), combined with a plasticization step using oligoethylene glycol dicarboxylic acid (OEGDA). This composite film exhibits a relatively high ionic conductivity of 9.5 x 10(-5) S/cm at 25 degrees C and 22% relative humidity. Detailed characterization of the composite was undertaken using grazing-angle Fourier transform infrared (GA-FTIR), atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 20 publications
3
50
1
1
Order By: Relevance
“…Whereas this self-assembly mechanism is able to produce extremely uniform films as thin as 1 nm per layer pair, because of the diffusive time scale it is not uncommon for a 25-layer-pair film to require more than 12 h to complete and thus is typically carried out by a computer-controlled slide stainer. 2 Furthermore, because LbL is typically based on an electrostatic phenomenon, the degree of ionization of each polyelectrolyte in solution, as determined by solution pH 4 or ionic strength, [5][6][7] has a profound effect on the strength of interaction felt with the surface and in turn the thickness of the adsorbed layer. 3 In the case of an absorbent substrate such as fabric, the cyclic nature of the dipping process can lead to carryover from the rinse baths to the proceeding polyelectrolyte solutions, inducing an unacceptable change in solution pH.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas this self-assembly mechanism is able to produce extremely uniform films as thin as 1 nm per layer pair, because of the diffusive time scale it is not uncommon for a 25-layer-pair film to require more than 12 h to complete and thus is typically carried out by a computer-controlled slide stainer. 2 Furthermore, because LbL is typically based on an electrostatic phenomenon, the degree of ionization of each polyelectrolyte in solution, as determined by solution pH 4 or ionic strength, [5][6][7] has a profound effect on the strength of interaction felt with the surface and in turn the thickness of the adsorbed layer. 3 In the case of an absorbent substrate such as fabric, the cyclic nature of the dipping process can lead to carryover from the rinse baths to the proceeding polyelectrolyte solutions, inducing an unacceptable change in solution pH.…”
Section: Introductionmentioning
confidence: 99%
“…Rubner et al reported that the microporous [25] or nanoporous polymer [26] thin films were developed from multilayer films of poly(allylamine hydrochloride) (PAH) and PAA, followed by a low pH aqueous treatment. Hammond et al [27] also created a 5 lm microporous film from 25 bilayers of linear PEI (LPEI) and PAA, by immersing into aqueous oligoethylene glycol dicarboxylic acid (OEGDA) at a pH range of 2.0-3.0. In those systems, the as-assembled polyelectrolyte films exhibited a nonporous film structure.…”
mentioning
confidence: 99%
“…[ 63 ] The process is very sensitive to the pH of the precursor solutions, and a mechanism is proposed whereby suppressed polyanion ionization results in a loss of ionic cross-links, and ultimately to a spinodal decomposition-like pore-forming event. Such fi lms have been investigated in solid electrolyte [ 64 ] and drug delivery [ 65 ] applications. Lutkenhaus et al have shown how post-formation changes in solution conditions may lead to a rich array of LbL fi lm pore structures, including the possibility of a gradient along the vertical direction, with pore sizes ranging from tens of nanometers to microns, and porosities from 0 to 77%.…”
Section: Methodsmentioning
confidence: 99%